Development and characterization of synthetic glucopyranosyl lipid adjuvant system as a vaccine adjuvant. - Rhea N Coler; Sylvie Bertholet; Magdalini Moutaftsi; Jeff A Guderian; Hillarie Plessner Windish; Susan L Baldwin; Elsa M Laughlin; Malcolm S Duthie; Christopher B Fox; Darrick Carter; Martin Friede; Thomas S Vedvick; et al. (PLoS ONE)
Innate immune responses to vaccine adjuvants based on lipopolysaccharide (LPS), a component of gram-negative bacterial cell walls, are driven by Toll-like receptor (TLR) 4 and adaptor proteins including MyD88 and TRIF, leading to the production of inflammatory cytokines, type I interferons, and chemokines. We report here on the characterization of a synthetic hexaacylated lipid A derivative, denoted as glucopyranosyl lipid adjuvant (GLA). We assessed the effects of GLA on murine and human dendritic cells (DC) by combining microarray, mRNA and protein multiplex assays and flow cytometry analyses. We demonstrate that GLA has multifunctional immunomodulatory activity similar to naturally-derived monophosphory lipid A (MPL) on murine DC, including the production of inflammatory cytokines, chemokines, DC maturation and antigen-presenting functions. In contrast, hexaacylated GLA was overall more potent on a molar basis than heterogeneous MPL when tested on human DC and peripheral blood mononuclear cells (PBMC). When administered in vivo, GLA enhanced the immunogenicity of co-administered recombinant antigens, producing strong cell-mediated immunity and a qualitative T(H)1 response. We conclude that the GLA adjuvant stimulates and directs innate and adaptive immune responses by inducing DC maturation and the concomitant release of pro-inflammatory cytokines and chemokines associated with immune cell trafficking, activities which have important implications for the development of future vaccine adjuvants.